THREE FAMOUS COFFEE SHOP LOGOS IN CIANJUR: AN APPROACH TO SEMIOTICAL ANALYSIS - Aulia, Fitria; Helmie, Jauhar (Jurnal JOEPALLT (Journal of English Pedagogy, Linguistics, Literature, and Teaching), 2020)
This research entilted “Semiotical on Three Famous Coffee Shop Logos in Cianjur”. The goals of this research is to describe the semiotic of logos at these coffee shop. Coffee shop usually has a logo to show the characteristics of the coffee shop and all identities or all aspects of the coffee shop. In this research, the researcher choose three logos of coffee shop in Cianjur. Then, to got the meaning of the logos the researcher analyzes them by using semiotic study. In this research, the researcher selected Tjerita Koffie, Ar7, and Imah Kopi. The result of this research discovers that the icon, index, and symbol are found in the logos. The iconic signs are mostly applied and the symbolic signs are used more than the indexical one. In accordance with the analysis, the three coffee shop represent their characteristics through their logos and the three logos of coffee shop show relationships between the signs semiotic and the history, concept, and goals of the cafes. Moreover, the three logos represent characteristics and relation between the sign semiotic of the logo and the history, concept, and goal of the coffee shop through their symbolic signs in their names.